Breast Reconstruction (IntechOpen, 2021)
In breast reconstruction, flap based procedures and implant based procedures are the two major modalities that have emerged as surgical options for patients. These are both continuing to evolve as new, innovative techniques help to improve outcomes and patient satisfaction. This book is divided into four sections. The first section includes overviews of mastectomy options and considerations in breast reconstruction procedure selection. The next section comprises non microsurgical reconstruction options which include implant based reconstruction refinements, the emerging role of fat grafting, and a novel technique of robotic latissimus flap harvesting. The third section is devoted to microsurgical reconstruction including flap refinements, tips and tricks, as well as advice on handling difficult situations. The final section includes the growing field of lymphedema surgery which is an important addition to breast reconstruction.